Identification of COPD Phenotypes and BODE Index of Mongolian Miners - Khishigdavaa, Garamjav; Dashjamts, Tuvshinjargal; Munkhtsetseg, Battulga; Jamsranjav, Javzmaa; Dashtseren, Ichinnorov (Central Asian Journal of Medical Sciences, 2019)
Objective: We aimed to investigate the relationship between COPD phenotypes and the BODE index. Methods: A cross-sectional study was performed in 99 patients with COPD. COPD was classified using HRCT into the three morphological phenotypes. Lung function was analyzed by spirometry and the BODE index (Body-mass index, airflow Obstruction, Dyspnea, and Exercise) was calculated. Results: According to the survey, 53 (53.5%) patients had A phenotype, 31 (31.3%) had a M phenotype, and 15 (15.1%) had a E phenotype. Emphysema type has higher BODE index scores. BODE index scores increased significantly with increasing severity of COPD according to the GOLD classification (P<.001). Conclusion: BODE index scores were increased in associating with severity of COPD. Emphysema type COPD has a worse BODE scores than others.